2011
DOI: 10.1007/s10096-011-1398-4
|View full text |Cite
|
Sign up to set email alerts
|

Viral aetiology of influenza-like illness in Belgium during the influenza A(H1N1)2009 pandemic

Abstract: The purpose of this investigation was to determine the proportion of influenza-like illness (ILI) attributable to specific viruses during the influenza A(H1N1)2009 pandemic and to describe the demographic and clinical characteristics of ILI due to respiratory viruses in Belgium. Nasopharyngeal swabs were collected from ILI patients by general practitioners (GPs) and paediatricians (PediSurv) and analysed for viruses. Of 139 samples collected from children <5 years of age by PediSurv, 86 were positive, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 20 publications
3
22
3
Order By: Relevance
“…up to 44z and 51z in previous reports), the number of children positive for HMPV was unexpectedly high (3,4). Hombrouck et al also found a remarkably high HMPV infection rate (14z of positives) during the pandemic; in contrast to our study, they excluded hospitalized patients (11).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…up to 44z and 51z in previous reports), the number of children positive for HMPV was unexpectedly high (3,4). Hombrouck et al also found a remarkably high HMPV infection rate (14z of positives) during the pandemic; in contrast to our study, they excluded hospitalized patients (11).…”
Section: Discussioncontrasting
confidence: 80%
“…A study of virus distribution in outpatients (including adults) in Belgium found pH1N1 to be the most common virus among children under the age of 5 years during the pandemic, probably reflecting a correlation between ILI case definition and actual influenza diagnosis. However, this group was frequently coinfected by other respiratory viruses (11). The rate of negative results in our study with respect to viral etiology was only 20z.…”
Section: Discussioncontrasting
confidence: 51%
“…As published in the literature, 15 a substantial proportion of the negative cases may have been caused by other viruses, but this was not assessed in the present study.…”
Section: Discussionmentioning
confidence: 61%
“…The 47 eligible publications are listed in Table . One quarter of these studies included children aged 0 to 5 years, and 6.4% and 12.8% of studies recruited children aged 0 to 3 years and aged 0 to 2 years, respectively.…”
Section: Resultsmentioning
confidence: 99%